A mechanisms-based explanation of nutrition policy (dis)integration processes in Uganda - Namugumya, Brenda Shenute; Candel, Jeroen J. L.; Talsma, Elise F.; Termeer, Catrien J. A. M. (Elsevier, 2020)
Many African governments have recently invested in strengthened nutrition policy integration to address malnutrition; as a step towards realising the targets of the Sustainable Development Goal 2. Previous studies have identified various factors that enable or constrain how nutrition integration occurs across policy sectors. However, the explanatory value of these studies has remained relatively limited, as the causal processes through which independent variables affect policy outcomes remain unelucidated. This paper addresses this gap by applying a causal mechanisms approach to investigate the processes that explain observed patterns of nutrition policy (dis)integration in different ministries in Uganda. We employed a process-tracing research design to reconstruct the context-mechanism configurations that explain the observed patterns of nutrition integration in Uganda between 2000 and 2017. Data was collected from interviews with 34 respondents, various policy and programming documents, and a focus group discussion. Our analysis reveals that increased nutrition policy integration is explained by four causal mechanisms: (1) international policy promotion; (2) issue promotion by international actors; (3) issue promotion by domestic policy entrepreneurs; and (4) instrumental policy learning. Conversely, two mechanisms led to policy disintegration: (1) leadership contestation; and (2) turf wars. All mechanisms proved activated by configurations of contextual conditions that were time- and organisation-specific. This study showed how a mechanisms approach can provide a more refined understanding of policy successes and failures in nutrition governance. Whereas integration-fostering mechanisms cannot be automated, both government and international actors working to scale up investments in nutrition need to consider and invest in the contextual conditions that allow for sustained nutrition policy integration and, ultimately, a more effective delivery of nutrition services. These include developing leadership for nutrition at different governance levels, domestic ownership and integration-fostering capacity, and supporting policy-oriented learning.